2012
DOI: 10.1353/jod.2012.0041
|View full text |Cite
|
Sign up to set email alerts
|

The Surprising Success of Multiparty Presidentialism

Abstract: The common wisdom is that when presidential political systems coincide with multiparty systems the result is gridlock; parties squabble and presidents are not able to stitch together the majorities they need to move forward with the business of governing. Latin America’s presidential systems were supposed to have been a disaster. Contrary to the conventional wisdom, however, presidentialism and multipartism seem to work rather well. E pur se muove , to quote Galileo. Over the last decade or so, multiparty pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 11 publications
0
28
0
6
Order By: Relevance
“…Attempting to reach out to the opposition through possible coalition formation seems to be an alternative. Based on recent analysis on the stability of multiparty presidentialism (Pereira and Melo, 2012), it is possible to speculate that a stable co-operation between the Mexican national executive with the national legislative rests on the ability of the PRI in strategically engaging with the PAN and PRD in key issues.…”
Section: The 2012 Presidential and Congressional Electoral Resultsmentioning
confidence: 99%
“…Attempting to reach out to the opposition through possible coalition formation seems to be an alternative. Based on recent analysis on the stability of multiparty presidentialism (Pereira and Melo, 2012), it is possible to speculate that a stable co-operation between the Mexican national executive with the national legislative rests on the ability of the PRI in strategically engaging with the PAN and PRD in key issues.…”
Section: The 2012 Presidential and Congressional Electoral Resultsmentioning
confidence: 99%
“…Many scholars suggested that the combination of presidential regimes and multiparty systems would result in political instability, thereby impeding the continuity of the new democratic regimes (Mainwaring 1993;Stepan and Skach 1993). Although those pessimistic predictions were not realised (Pereira and Melo 2012), tensions between the executive and legislative branches of government remained central to analyses of Latin American presidential regimes (Alemán and Navia 2009). For this reason, studies of Latin American presidential institutions have focused on testing hypotheses that were first developed in the American literature and then adapted to the specificities of Latin American politics, especially the multiparty system.…”
Section: American Presidentsmentioning
confidence: 99%
“…Presidents in Latin America can introduce bills, veto laws, legislate by decree during emergencies, and have preeminence in the making of annual budgets (Mainwaring and Shugart, 1997;Shugart and Carey, 1992). As a result, presidents have been endowed with larger legislative powers to get their policy agenda passed (Pereira and Melo, 2012) and this has helped the executive to win greater leverage vis-à-vis the legislature over time (Mustapic, 1997). Constitutional reforms after the third wave of democratization have systematically enlarged presidential agenda power (Negretto, 2009).…”
Section: The Role Of Congress Presidents and Governors In Distributmentioning
confidence: 99%